2018
DOI: 10.1073/pnas.1807123115
|View full text |Cite
|
Sign up to set email alerts
|

Permanent neuroglial remodeling of the retina following infiltration of CSF1R inhibition-resistant peripheral monocytes

Abstract: SignificanceThis work contributes to the understanding of the enigmatic progressive retinal damage following acute ocular surface injury. Clinical findings in patients suggest that such injuries can adversely affect the retina. This study demonstrates that corneal injury leads to rapid infiltration of blood-derived monocytes into the retina and to subsequent remodeling of the neuroglial system. In contrast to previously held belief, this study shows that the blood-derived monocytes engraft permanently into the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 66 publications
5
38
0
Order By: Relevance
“…We reject the comment by Green and Hume ( 4 ) that PLX5622 dose and duration was not provided or that it was selected arbitrarily. A careful reading of our paper ( 1 ) and the literature reveals this information, which is in concordance with at least 14 papers using exactly the same dose (PLX5622 chow, 1,200 ppm) and duration (3 wk) ( 1 3 , 5 ), some of which have been cited by Green et al ( 6 ) in a prior review. † For the benefit of the community, we provide additional data in this Reply showing that even short-term (7 d or 10 d) treatment with PLX5622 results in similar nonmicroglia changes ( Figs.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…We reject the comment by Green and Hume ( 4 ) that PLX5622 dose and duration was not provided or that it was selected arbitrarily. A careful reading of our paper ( 1 ) and the literature reveals this information, which is in concordance with at least 14 papers using exactly the same dose (PLX5622 chow, 1,200 ppm) and duration (3 wk) ( 1 3 , 5 ), some of which have been cited by Green et al ( 6 ) in a prior review. † For the benefit of the community, we provide additional data in this Reply showing that even short-term (7 d or 10 d) treatment with PLX5622 results in similar nonmicroglia changes ( Figs.…”
supporting
confidence: 82%
“…Many microglia papers have assumed or claimed that CSFR1 inhibition has no to minimal effects on peripheral immune cells. * The nonmicroglia effects of CSFR1 inhibition have direct ramifications for the interpretation of relevant experimental data; peripheral monocytes/macrophages engraft permanently into the retina after PLX5622 treatment ( 2 , 3 ), causing remodeling and functional changes that affect studied outcome.…”
mentioning
confidence: 99%
“…Extravasation and increased monocyte infiltration have been demonstrated as an early and persistent feature of glaucoma in animal models 33 and in post mortem human tissue, 2 and CD45 hi monocytes are present in the retina in low numbers under normal physiologic conditions. 34 , 35 We observed IsoB4+ fully amoeboid cells (devoid of any dendritic processes) in the majority of retinas in all experimental groups, but demonstrate no significant change in the average monocyte density across experimental groups ( Fig. 5 C).…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, previous studies have shown that under certain conditions (e.g. in an empty microglial niche) induced by microglial depletion, peripheral myeloid cells can infiltrate and serve as the source for microglial repopulation in the brain parenchyma [40][41][42][43] . Thus, we reasoned that repopulation could be occurring from peripheral sources and undertook several complementary experimental approaches to explore this.…”
Section: End Repopulating Cells Do Not Derive From the Peripherymentioning
confidence: 99%